2007
DOI: 10.1080/14017430701302482
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide in individuals with normal left ventricular systolic function

Abstract: The myocardium regularly produces or releases CNP in patients with normal LV systolic function. Brief periods of rapid RA pacing, PSVT, or EPS does not change the production and/or release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…In addition to supporting previous (and smaller) studies showing net cardiac release of CNP, 22,24,25 the present study relates these findings to cardiac function and reports new findings of CNP release by head and neck and lower limb tissues and extraction of CNP across hepatic, renal, and pulmonary tissues in adult humans.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to supporting previous (and smaller) studies showing net cardiac release of CNP, 22,24,25 the present study relates these findings to cardiac function and reports new findings of CNP release by head and neck and lower limb tissues and extraction of CNP across hepatic, renal, and pulmonary tissues in adult humans.…”
Section: Discussionsupporting
confidence: 67%
“…Recent work, however, has shown that clinical states of cardiac impairment are associated with increases in circulating and coronary sinus CNP levels, 20 -22 which suggest that elevated cardiac tissue production of CNP may be associated with increasing myocardial dysfunction. Although individual studies have separately measured transcardiac [22][23][24][25] and transrenal 26 CNP immunoreactivity, little is known about CNP production and clearance across other organs in health or cardiovascular disease. Such studies have been hindered by the largely autocrine/paracrine nature of CNP with rapid local (and systemic) degradation through uptake by the clearance receptor 27 and hydrolysis by neprilysin and consequent very low circulating concentrations of CNP.…”
mentioning
confidence: 99%
“…Our laboratory previously found that the myocardium regularly produced or released CNP in patients with normal left ventricular (LV) systolic function. Brief periods of rapid right atrial (RA) pacing (with pacing cycle lengths starting from 750 ms, in 50-ms decrement, to a minimum of 400 ms, each for 2 min and rest for 2 min) or PSVT (sustained Ͻ2 min) did not change the production and/or release (13). The aim of this study was to compare the response of the three peptides against a 30-min induced PSVT.…”
mentioning
confidence: 99%
“…Kuo et al28) reported that the myocardium regularly produces or releases CNP in patients with symptomatic paroxysmal supraventricular tachycardia (PSVT) and normal left ventricular systolic function and brief periods of rapid atrial pacing, and that PSVT or electrophysiological studies did not change the production and/or release of CNP. Lupattelli et al29) suggested that CNP was not altered in patients affected by hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%